PERAN MEDIA MASSA DALAM PERKEMBANGAN PUISI INDONESIA MODERN SEBELUM KEMERDEKAAN - Mahmud, Amir (ATAVISME, 2007)
Pre-independence poems have been categorized as a struggle against the government and, on the other side, as a media to increase the nationalism of young natives to their country and nation. In the subsequent development, poem column in magazines is not only used as a media of poets creativity but also used as a media in propagandizing dissatisfaction to the colonialist. Native people not only need creativity space but also want to get a sense of justice, to get herness, freedom in expressing an opinion, and freedom from as an instrument of propaganda which fights for right to live free from the colonialist fetters. In addition to used as media to struggle, advice, propagandize, and get justice, pre-independence poem is also used to express the intellectual ideas of the young.